CSF sAPPβ, YKL-40, and neurofilament light in frontotemporal lobar degeneration. (11th July 2017) - Alcolea, Daniel; Vilaplana, Eduard; Suárez-Calvet, Marc; Illán-Gala, Ignacio; Blesa, Rafael; Clarimón, Jordi; Lladó, Albert; Sánchez-Valle, Raquel; Molinuevo, José L.; García-Ribas, Guillermo; Compta, Yaroslau; Martí, María José; et al.
Abstract : Objective: To analyze the clinical utility of 3 CSF biomarkers and their structural imaging correlates in a large cohort of patients with different dementia and parkinsonian syndromes within the spectrum of frontotemporal lobar degeneration (FTLD). Methods: We analyzed 3 CSF biomarkers (YKL-40, soluble β fragment of amyloid precursor protein [sAPPβ], neurofilament light [NfL]) and core Alzheimer disease (AD) biomarkers (β-amyloid1-42, total tau, phosphorylated tau) in patients with FTLD-related clinical syndromes (n = 159): behavioral variant of frontotemporal dementia (n = 68), nonfluent (n = 23) and semantic (n = 19) variants of primary progressive aphasia, progressive supranuclear palsy (n = 28), and corticobasal syndrome (n = 21). We also included patients with AD (n = 72) and cognitively normal controls (CN; n = 76). We compared cross-sectional biomarker levels between groups, studied their correlation with cortical thickness, and evaluated their potential diagnostic utility. Results: Patients with FTLD-related syndromes had lower levels of sAPPβ than CN and patients with AD. The levels of sAPPβ showed a strong correlation with cortical structural changes in frontal and cingulate areas. NfL and YKL-40 levels were high in both the FTLD and AD groups compared to controls. In the receiver operating characteristic analysis, the sAPPβ/YKL-40 and NfL/sAPPβ ratios had areas under the curve of 0.91 and 0.96, respectively, distinguishing patients with FTLD from CN, and of 0.84 and 0.85, distinguishing patients with FTLD from patients with AD. Conclusions: The combination of sAPPβ with YKL-40 and with NfL in CSF could be useful to increase the certainty of the diagnosis of FTLD-related syndromes in clinical practice. Classification of evidence: This study provides Class III evidence that CSF levels of sAPPβ, YKL-40, and NfL are useful to identify patients with FTLD-related syndromes.